TERAPI MENULIS EKSPRESIF SEBAGAI MEDIA KATARSIS DALAM MENGURANGI KECEMASAN: SYSTEMATIC LITERATURE REVIEW - Falia, Falia Nur Arviani; Kholil, Kholil Lur Rochman (JIEGC Journal of Islamic Education Guidance and Counselling, 2024)
Anxiety disorders are the most common mental disorders experienced by individuals ranging from children, teenagers to adults. This anxiety disorder can disrupt an individual's daily activities if not treated immediately. Therefore, there is a need for a way to help deal with this problem, one of which is expressive writing therapy. Researchers in conducting research used the systematic literature review (SLR) method, namely by reviewing 10 journals that were relevant to the research theme. The researcher's aim in conducting this research is to describe expressive writing therapy as a method in psychology that can be used as a medium of catharsis for individuals who are experiencing anxiety. After the researchers reviewed 10 journals, the results showed that this expressive writing therapy has been proven to be effective and useful as a medium for channeling emotions (catharsis) for individuals who are experiencing anxiety. Writing therapy can be used as a method to express thoughts, feelings, emotions that may be difficult to explain orally so that you can express them in written form. So that after carrying out this therapy an individual can feel comfortable, relieved and not have burdened thoughts or feelings because they have been expressed and expressed in the right way.